Managing Multiorgan Failure in Acute on Chronic Liver Failure - Pompili, Enrico; Iannone, Giulia; Carrello, Daniele; Zaccherini, Giacomo; Baldassarre, Maurizio; Caraceni, Paolo (Seminars in Liver Disease, 2024)
Acute-on-chronic liver failure (ACLF) is defined as a clinical syndrome that develops in patients with chronic liver disease characterized by the presence of organ failure and high short-term mortality, although there is still no worldwide consensus on diagnostic criteria. Management of ACLF is mainly based on treatment of “precipitating factors” (the most common are infections, alcohol-associated hepatitis, hepatitis B flare, and bleeding) and support of organ failure, which often requires admission to the intensive care unit. Liver transplantation should be considered in patients with ACLF grades 2 to 3 as a potentially life-saving treatment. When a transplant is not indicated, palliative care should be considered after 3 to 7 days of full organ support in patients with at least four organ failures or a CLIF-C ACLF score of >70. This review summarizes the current knowledge on the management of organ failure in patients with ACLF, focusing on recent advances.
Keywords: ACLF; acute decompensation; cirrhosis; hepatology; liver transplantation